2013
DOI: 10.1021/cg3013359
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Dissolution of Crystal under Load: New Experimental Results on KCl

Abstract: From the first experiments of Lavalle in 1853, it has been concluded, following Taber and Correns's publications, that a growing crystal can exert a linear pressure. This pressure has long been accounted for the stone degradation by salt crystal, as observed on cultural heritage objects. Nevertheless, according to both Riecke's principle and crystal growth theories, a mechanically constrained crystal has a higher solubility than an unstressed one; since the local supersaturation is reduced, the loaded faces ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…that precipitation preferentially occurs on unstressed surfaces). However, experiments have indicated that, for example, for uniaxially loaded crystals, dissolution will occur near the axial load application and reprecipitate along the traction‐free transverse surfaces on the same, stressed crystal. For a crystal with a smooth loading surface, one may readily show that the axial stress is the same directly under the load application (where dissolution is observed) and along the traction‐free transverse surfaces (where precipitation is observed).…”
Section: Computational Implementationmentioning
confidence: 99%
“…that precipitation preferentially occurs on unstressed surfaces). However, experiments have indicated that, for example, for uniaxially loaded crystals, dissolution will occur near the axial load application and reprecipitate along the traction‐free transverse surfaces on the same, stressed crystal. For a crystal with a smooth loading surface, one may readily show that the axial stress is the same directly under the load application (where dissolution is observed) and along the traction‐free transverse surfaces (where precipitation is observed).…”
Section: Computational Implementationmentioning
confidence: 99%
“…It is generally accepted that material damage occurs when the tensile stress caused by the crystals growing in the confined space of the porous matrix exerts a pressure that is greater than the tensile strength of the porous material [32][33][34][35][36].…”
Section: Fundamental Mechanisms and Influencing Factors For Salt Crysmentioning
confidence: 99%
“…The ability of salt to induce damage relies more specifically on the presence (at least temporary) of a supersaturated solution, and ultimately a layer (δ), between the pore walls and the crystal formation, which enables the diffusion of ions contributing to the continued growing crystal surfaces [32][33][34][35][36] ( Figure 2). The solution layer is provided by the action of repulsive forces, or "disjoining pressure", between the growing salt crystal and the pore wall.…”
Section: Fundamental Mechanisms and Influencing Factors For Salt Crysmentioning
confidence: 99%
“…This and experimental shortcomings raised [19,20] -as well as the failure of other researchers to directly measure crystallization pressure [21,22] -led to questioning the concept altogether. More recently, Desarnaud et al [23] used a novel experimental approach to directly quantify the crystallization pressure.…”
Section: Measurement Of Crystallization Pressurementioning
confidence: 99%